Pengaruh Due Professional Care, Akuntabilitas, Kompleksitas Audit, dan Time Budget Pressure Terhadap Kualitas Audit - Ratha, I Made Dwi Kresna; Ramantha, I Wayan (E-Jurnal Akuntansi, 2015)
This study was conducted to determine the effect of due professional care,. accountability,. the complexity of the audit,. and time budget pressure on audit quality in the public accounting firm in Denpasar. Source of data in this study are primary data in the form of answers to the questionnaire to the auditor KAP in Denpasar and secondary data in the form of the number of auditors KAP in Denpasar and the list of names public accounting firm. Method of determining the sample in this study using purposive sampling method and the method that meets the criteria as much as 50 samples. Data analysis techniques in this study using multiple linear regression analysis, where the results showed a variable due professional care, accountability positive effect on audit quality, while the variable complexity of the audit and the time budget pressure negatively affect audit quality .
Keywords: Due Professional Care, Accountability, Audit Complexity, Time Budget Pressure, and Audit Quality